ANALISIS PENGARUH PERSEPSI HARGA, KEPERCAYAAN PELANGGAN, KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Waroeng Steak & Shake Semarang Cabang Kelud) - Chendradewi, Ranny; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2016)
The rapid development of the culinary business in the city of Semarang is also supported by consumer behavior itself. Family cities tend to be practical, they choose instant food and liked the restaurant with atmosphere